Menautkan Bukti Matematika dalam Konstruktivisme - Sabri Sabri (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2012)
DOWNLOAD PDFAn understanding of constructivism would be complete when it could be implemented within professional practice. Taking into account the current philosophies in mathematics education, I can see a possible setting which can be generated by using constructivism as a mediator. This mediator is used to set the context in which the processes of teaching and learning of mathematical proof are conducted.   Key words: Constructivism, mathematical proof, teaching and learning.